Glass source book - Marshall, Jo. (London : Collins and Brown, 1990)
Records the world's great glassmaking traditions, including Egypt, Rome, and Islam, the age of Venetian supremacy, the seventeenth and eighteenth centuries, the industrial age, the art nouveau era, and the twentieth century.
Egypt, Rome and Islam -- The Venetian Supremacy -- The 17th and 18th Centuries -- The Industrial Age -- The Art Nouveau Era -- The 20th Century.
Includes Index.
Keywords: Glassware